A new optimization procedure of heaving point absorber hydrodynamic performances. (1st April 2016) - Piscopo, V.; Benassai, G.; Cozzolino, L.; Della Morte, R.; Scamardella, A.
Abstract: A new procedure to optimize the hydrodynamic performances of heaving point absorbers is outlined, with the main aim of maximising the yearly energy production, based on the wave climate representative of the candidate deployment site. Phase control is applied, adding a fully submerged mass to the wave energy converter, to properly shift the device heave natural frequency, gain resonance with the most energetic waves and maximize the energy absorption. The optimization procedure allows for varying the fully submerged added mass and the Power Take Off damping, until the optimum configuration is detected. The incidence of buoy dimensions on both device efficiency and energy production costs is fully discussed and investigated. In this respect, a new parameter, namely the Annualised Energy Production per unit area, is proposed to detect, in a preliminary project phase, the minimum cost configuration, without detailing the device cost breakdown that, in turn, is required to estimate the Levelised Cost of Energy. The optimization procedure is applied to a deployment site located in Tyrrhenian Sea, off Southern Italy coastlines, varying the buoy dimensions in the range 4–8 m, with 1 m step. Both hydrodynamic results, detection of optimum device configuration and cost analysis are fully discussed. Highlights: Optimization of heaving point absorber hydrodynamic performances by phase control under a slamming restraint condition. Incidence of fully submerged added mass and PTO damping on the device yearly energy absorption. Detection of minimum cost configuration by the Annualised Energy Production per unit area parameter. Preliminary evaluation of Levelised Cost of Energy as a function of plant capacity. Parametric analysis for a candidate deployment site located in Southern Tyrrhenian Sea.